Second hyperpolarizability of hexagonal graphene quantum dots: Effects of size and structural defects. (July 2021) - Zhou, Jiasheng; Li, Haipeng; Yang, Ziqiang; Zhang, Zitao; Shen, Xiaopeng; Han, Kui
Highlights: The size and edge effects on the three-order NLO properties of graphene quantum dots are studied. The structural defects play important role in the electronic and three-order NLO properties of the graphene quantum dots. Stone-Wales defects can enhance the second hyperpolarizability of graphene quantum dots due to the reduced energy gap. Abstract: Graphene quantum dots (GQDs) are nanosized fragments of graphene containing a bandgap caused by edge effects and quantum confinement. These features enable GQDs to have attractive photonics applications. During the preparation of graphene nanostructures, defects are unavoidable as they influence the behavior of π-electron transfer, which in turn impact the nonlinear optical (NLO) response. Herein, density functional theory was used to determine the electronic and three-order NLO properties of hexagonal GQDs with structural defects. The size of GQDs and the edge effects on their NLO properties were also investigated. Results showed with increased molecule size, the second hyperpolarizability increased for zigzag- and armchair-edged GQDs. This finding was due to the decrease in their frontier molecular-orbital energy gaps. Moreover, the introduction of point vacancy limited the π-electron transport in the zigzag-edged GQD, thereby widening the frontier molecular-orbital energy gap compared with the perfect zigzag-edged GQDs. However, in the presence of zigzag-edged GQDs having Stone–Wales defects, the energy gap decreased; consequently, the NLO response improved. All these findings provided new insights into the design of novel graphene-based NLO materials that may help expand the applications of GQDs in optoelectronic nanodevices. Graphical abstract: Image, graphical abstract